2023
DOI: 10.1177/10815589221145043
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine pesticides, oxidative stress biomarkers, and leukemia: a case–control study

Abstract: Exposure to pesticides has been linked to an elevated risk of leukemia. The present research aimed to evaluate the relationship between organochlorine (OC) pesticides and biomarkers of oxidative stress in leukemia patients. This work was conducted on 109 patients with leukemia and 109 healthy controls. The serum concentrations of seven derivatives of OCs including alpha-HCH, beta-HCH, gamma-HCH, 2,4-DDT, 4,4-DDT, 2,4-DDE, and 4,4-DDE along with acetylcholinesterase (AChE), glutathione peroxidase (GPx), superox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…To terminate the reaction, 2.5 mL of the DDA reagent (potassium dichromate solution 5% and glacial acetic acid) was added (at a ratio of 1:3 v/v). Finally, the absorbance of the reaction mixture was measured at 570 nm ( Rafeeinia et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…To terminate the reaction, 2.5 mL of the DDA reagent (potassium dichromate solution 5% and glacial acetic acid) was added (at a ratio of 1:3 v/v). Finally, the absorbance of the reaction mixture was measured at 570 nm ( Rafeeinia et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…After that, the reaction was terminated by adding 2.5 mL of the DDA reagent (potassium dichromate solution 5% with glacial acetic acid) (1:3 v/v). Finally, the absorbance of the reaction mixture was evaluated at 570 nm ( Rafeeinia et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“… 32 According to studies, MDA and HNE were higher in the leukemia cohort compared with the normal cohort. 33 , 34 Research has shown that HNE reduces oxidative damage in tumor by reducing ROS production through activation of uncoupling Protein (UCP). 35 In addition, excessive formation of HNE can affect mitochondrial function and eventually lead to cell death.…”
Section: Ros‐mediated Aml Gene Alterationsmentioning
confidence: 99%
“…ROS‐mediated oxidation of polyunsaturated fatty acids (PUFA) causes lipid peroxidation, the main products of which are malondialdehyde (MDA) and 4‐hydroxy‐2‐nonenal (HNE) 32 . According to studies, MDA and HNE were higher in the leukemia cohort compared with the normal cohort 33,34 . Research has shown that HNE reduces oxidative damage in tumor by reducing ROS production through activation of uncoupling Protein (UCP) 35 .…”
Section: Ros‐mediated Aml Gene Alterationsmentioning
confidence: 99%